2019
DOI: 10.1158/1541-7786.mcr-18-1127
|View full text |Cite
|
Sign up to set email alerts
|

HBx-K130M/V131I Promotes Liver Cancer in Transgenic Mice via AKT/FOXO1 Signaling Pathway and Arachidonic Acid Metabolism

Abstract: Chronic hepatitis B viral (HBV) infection remains a high underlying cause for hepatocellular carcinoma (HCC) worldwide, while the genetic mechanisms behind this remain unclear. This study elucidated the mechanisms contributing to tumor development induced by the HBV X (HBx) gene of predominantly Asian genotype B HBV and its common HBx variants. To compare the potential tumorigenic effects of K130M/V131I (Mut) and wild-type (WT) HBx on HCC, the Sleeping Beauty (SB) transposon system was used to deliver HBx Mut … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…Coincidentally, HBx may promote proliferation of liver cells by altering the expression of genes that participated in arachidonic acid metabolism 46 . Our group has reported that the integration of HBx fragment can be detected in clinical hepatocellular carcinoma tissues 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Coincidentally, HBx may promote proliferation of liver cells by altering the expression of genes that participated in arachidonic acid metabolism 46 . Our group has reported that the integration of HBx fragment can be detected in clinical hepatocellular carcinoma tissues 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence showed that the PHLPP family members could suppress the tumorigenesis, because of their involvements in the blockage of growth factor‐induced signaling pathway by the attenuation of AKT signaling . FOXO1 was also highlighted to be a downstream target of AKT signaling to suppress tumor development . Huang et al reported that PHLPP2 displayed an important effect on the invasiveness of BC cells by the regulation of lncRNA MEG3/miR‐27a axis .…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, Akt also enhanced MDM2-mediated ubiquitination leading to p53 (TP53) degradation [ 87 ] and catalyzed the nuclear localization and stabilization of BCL3 by phosphorylation [ 79 ], where BCL3 is the aforementioned transcription coregulator having been proven to interact with NF-κB so as to facilitate its transcriptional ability. Moreover, it even caused nuclear exclusion and cellular dysfunctions of FoxO proteins through phosphorylation and repression [ 88 ]. Therefore, as the identified target genes of FoxO proteins in the core host/pathogen cross-talk pathways, BNIP3, BMI1, SOD2, and cyclin-dependent kinase inhibitor 1 (CDKN1A) encoding p21, might probably be down-regulated.…”
Section: Resultsmentioning
confidence: 99%